An Electron Microscopic Study of Platelet Thrombus Formation in the Rabbit with Particular Regard to 5-Hydroxytryptamine Release - Baumgartner, H. R; Tranzer, J. P; Studer, A (Thrombosis and Haemostasis, 1967)
Electron microscopic and histologic examination of rabbit ear vein segments 4 and 30 min after slight endothelial damage have yielded the following findings :1. Platelets do not adhere to damaged endothelial cells.2. If the vessel wall is denuded of the whole endothelial cell, platelets adhere to the intimai basement lamina as do endothelial cells.3. The distance between adherent platelets as well as endothelial cells and intimai basement lamina measures 10 to 20 mµ, whereas the distance between aggregated platelets is 30 to 60 mµ.4. 5-hydroxytryptamine (5-HT) is released from platelets during viscous metamorphosis at least in part as 5-HT organelles.It should be noted that the presence of collagen fibers is not necessary for platelet thrombus formation in vivo.